O-006 Histotripsy for intracerebral hemorrhage in a porcine model. (4th August 2020) - Gerhardson, T; Sukovich, J; Chaudhary, N; Chenevert, T; Ives, K; Hall, T; Camelo-Piragua, S; Daou, B; Xu, Z; Pandey, A
Abstract : Introduction: Histotripsy is a noninvasive, focused ultrasound technique that generates cavitation to mechanically fractionate tissue. Intracerebral hemorrhage (ICH) is characterized by a 30-d mortality rate of 40% and significant disability for those who survive. Histotripsy has the potential to liquefy clot in the brain and facilitate minimally invasive aspiration. We aim to investigate the initial safety concerns of histotripsy mediated clot liquefaction and aspiration in a porcine ICH model. Methods: About 1.75-mL clots were formed in the frontal lobe of the brain (n=18; n=6/group). The centers of the clots were liquefied with histotripsy 48 h after formation, and the content was either evacuated or left within the brain. A control group was left untreated. Pigs underwent magnetic resonance imaging (MRI) 7 to 8 d after clot formation and were subsequently euthanized. Neurological behavior was assessed throughout. Histological analysis was performed on harvested brains. A subset of pigs underwent acute analysis (≤6 h). Results: Histotripsy was able to liquefy the center of clots without direct damage to the perihematomal brain tissue. An average volume of 0.9 ± 0.5 mL was drained after histotripsy treatment. All groups showed mild ischemia and gliosis in the perihematomal region; however, there were no deaths or signs of neurological dysfunction in any groups. Conclusion: This study presents the first analysis of histotripsy-based liquefaction of ICH in vivo. Histotripsy safely liquefies clots without significant additional damage to the perihematomal region. The liquefied content of the clot can be easily evacuated, and the undrained clot has no effect on pig survival or neurological behavior. Disclosures: T. Gerhardson: None. J. Sukovich: None. N. Chaudhary: None. T. Chenevert: None. K. Ives: None. T. Hall: None. S. Camelo-Piragua: None. B. Daou: None. Z. Xu: None. A. Pandey: None.